2017
DOI: 10.15761/ogr.1000116
|View full text |Cite
|
Sign up to set email alerts
|

Association of low levels of first trimester Pregnancy Associated Plasma Protein (PAPP-A) with adverse pregnancy outcomes: An observational study

Abstract: Objectives: To explore the effects of low levels of first trimester Pregnancy Associated Plasma Protein-A (PAPP-A) on adverse pregnancy outcomes.Design: Single centre retrospective observational study. Setting: District general hospital.Population: Women with singleton pregnancies with low PAPP-A, attending Heatherwood and Wexham Park Hospital for first trimester combined screening for Down syndrome.Methods: Data was collected from Astraia Database and CMiS maternity system. Multiple linear regression models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Almost 17% of a newborn in the target group were small for gestational age below the 10 th percentile, higher than in Thompson study-7.44% [20]. Some studies show a significant difference in an adverse outcome in a group with PAPP-A below 0.4 MoM, probably because of different statistical power [21], [22].…”
Section: Discussionmentioning
confidence: 87%
“…Almost 17% of a newborn in the target group were small for gestational age below the 10 th percentile, higher than in Thompson study-7.44% [20]. Some studies show a significant difference in an adverse outcome in a group with PAPP-A below 0.4 MoM, probably because of different statistical power [21], [22].…”
Section: Discussionmentioning
confidence: 87%
“…(2017) showed that MoM PAPP-A ≤0.4 is associated with SGA <10 th centile at P = 0.04 with a positive predictive value of 83.3% and negative predictive value of 79.3%. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…PAPP-A is also a glycoprotein, which is mainly produced by syncytiotrophoblast[ 8 ] and may affect placental function through insulin-like growth factors (IGFs) because PAPP-A is a protease for IGF binding protein (IGFBP) 4 and 5. The IGFBPs inhibit the action of IGFs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show a significant difference in an adverse outcome in a group with PAPP-A below 0.4 MoM, probably because of different statistical power [21], [22].…”
Section: Discussionmentioning
confidence: 99%